Features of indirect speech acts with the meaning of motivation in Russian prose of the 1920s - Михальчук, Наталья Александровна (Journal of the Belarusian State University. Philology, 2024)
Indirect speech acts with the generalised meaning of motivation in the works of Russian writers of the 1920s are studied. Ritualised and non-ritualised types in private discourse are identified and differentiated. It is substantiated that indirect motives in the literary text of the indicated period are characterised by means of modality with the meaning of obligation, constructions with forms of the subjunctive mood, with lexemes want, desire. Tactics for softening the intention of motivation have been identified, and the reasons for using indirect statements with this meaning have been identified. As features of the use of indirect motives in Russian prose of the 1920s tendencies towards an I-oriented speech behaviour, towards politeness, and towards the use of categorical implementations of intentions are named.